Energy and exergy analyses of a submerged arc furnace used for ferrochrome production - Kapan, Sinan; Celik, Nevin; Camdali, Unal; Taskiran, Ali (Inderscience Enterprises Ltd, 2024)
In this study submerged arc furnace (SAF) of an important ferrochrome production facility in Elazig-Turkey is discussed. The 1st and 2nd laws of thermodynamics are applied to the SAF in which smelting processes of chrome ore are carried out. It has been concluded that, the energy efficiency of the SAF in the facility is 50.69% and the exergy efficiency is 46.49%. The energy losses are nearly 5.85% of the total energy entering into the control volume, and the exergy losses is 20.39% of the total exergy input. The results show that there are some areas to improve the energy and exergy efficiencies. The energy efficiency is 50.69%. The exergy efficiency is 46.49%. Lost energy is 182.85 GJ. Lost exergy is 831.16 GJ.
Keywords: energy and exergy analysis; high carbon ferrochrome; submerged arc furnace; SAF